Which Inequality Matters? Growth Evidence Based on Small Area Welfare Estimates in Uganda - Schipper, Youdi; Hoogeveen, Johannes G. (World Bank, Washington, DC, 2012)
Existing empirical studies on the relation between inequality and growth have been criticized for their focus on income inequality and their use of cross-country data sets. Schipper and Hoogeveen use two sets of small area welfare estimates-often referred to as poverty maps-to estimate a model of rural per capita expenditure growth for Uganda between 1992 and 1999. They estimate the growth effects of expenditure and education inequality while controlling for other factors, such as initial levels of expenditure and human capital, family characteristics, and unobserved spatial heterogeneity. The authors correct standard errors to reflect the uncertainty due to the fact that they use estimates rather than observations. They find that per capita expenditure growth in rural Uganda is affected positively by the level of education as well as by the degree of education inequality. Expenditure inequality does not have a significant impact on growth.